Variability in sterility mosaic pathogen of pigeonpea in India - J.Y. ASTAPUTRE4, B.K. SINHA5, Y. MUNIYAPPA6, M.Y . REDDY1, T.N. RAJU1, Y.L. NENE1, A.M. GHANEKAR1, K.S. AMIN2, G. ARJUNAN3; KAUSALYA GANGADHARAN8, S.Y. REDDY1, R.P. GUPTA7 and (Indian Phytopathology, 2002)
Between 1987 and 1990, sixteen pigeonpea genotypes were tested for their reaction to isolates of the sterility mosaic pathogen from nine disease endemic locations in India. The genotypes were tested in pot or field experiments at the nine respective locations and also by inoculating the genotypes with all the nine isolates in pot experiments at the Hyderabad location. There was a large variation in disease incidence and symptom expression of the genotypes between the locations and between the seasons, and tests at the respective location and at Hyderabad. The variation in symptom expression was comparatively less than disease incidence. Based on the reaction of seven genotypes (ICP 2376, ICP 7035, ICP 8862, ICP 8863, ICP 10976, ICP 10984. ICP 11146) in 51 field and pot tests, the nine isolates were grouped into five distinct variants. The isolate from Gwalior was designated as variant 1; Badnapur and Patancheru isolates represent variant 2; Coimbatore, Kumarganj and Pudukottai isolates represent variant 3; Bangalore and Dholi isolates represent variant 4; and Kanpur isolate represents variant 5.